Delivery, maternal and neonatal outcomes in nulliparous women with gestational diabetes undergoing epidural labour analgesia: a propensity score-matched analysis. Issue 7 (29th July 2022) - Chen, Yu; Ye, Xin; Wu, Han; Yuan, Xueling; Yu, Xiaofang; Wu, Huanghui; Wu, Xiaodan; Chen, Yanqing
Abstract : Objective: This study aimed to retrospectively analyse the influence of epidural labour analgesia (ELA) on delivery and maternal and neonatal outcomes in nulliparous women with gestational diabetes mellitus (GDM) using propensity score-matched analysis. Design: Retrospective cohort analysis. Setting: Primary care practices in a teaching hospital from March 2018 to October 2021. Participants: A total of 816 delivery records of nulliparous women with GDM were collected and retrospectively analysed. Interventions: ELA and non-ELA (NELA) cohorts were assessed. Main outcome measure: The primary outcome assessed was delivery type (spontaneous, assisted vaginal or caesarean). The secondary outcomes assessed included labour duration and maternal and neonatal outcomes. Results: A total of 137 propensity score-matched pairs of ELA and NELA patients were analysed. ELA was associated with a decreased rate of caesarean section (18.3% vs 46.0% in the ELA vs NELA cohort, respectively; p<0.05) and an increased occurrence of assisted vaginal delivery (35.8% vs 12.4% in the ELA vs NELA cohort, respectively; p<0.05). The duration of the first and total stages of labour was prolonged, the occurrence of postpartum fever increased, and the duration of hospital stay was shortened in those receiving ELA (all p<0.05). Additionally, neonatal birth weight, plasma glucose levels and neonatal macrosomia occurrence increased, while neonatal intensive care unit admissions and neonatal hypoglycaemia decreased in the ELA versus the NELA group (all p<0.05). With respect to other maternal and neonatal outcomes, both cohorts were similar. Conclusions: The use of ELA decreases the rate of caesarean section and improves maternal and neonatal outcomes in nulliparous women with GDM. Trial registration number: ChiCTR-2000033091.